2023
DOI: 10.3390/en16031518
|View full text |Cite
|
Sign up to set email alerts
|

MIMO-SAR Interferometric Measurements for Wind Turbine Tower Deformation Monitoring

Abstract: Deformations affect the structural integrity of wind turbine towers. The health of such structures is thus assessed by monitoring. The majority of sensors used for this purpose are costly and require in situ installations. We investigated whether Multiple-Input Multiple-Output Synthetic Aperture Radar (MIMO-SAR) sensors can be used to monitor wind turbine towers. We used an automotive-grade, low-cost, off-the-shelf MIMO-SAR sensor operating in the W-band with an acquisition frequency of 100 Hz to derive Line-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The results obtained from MIMO radar interferometric processing were used as a benchmark and for comparison. Previous studies have shown that radar observations exhibit a high correlation with vision-based methods and accelerometers, with a maximum error of approximately 0.02 mm [5,7]. Our simulations revealed that while the resolutions of the AoA and vibration frequency improved with an increasing observation length, the resolution of the vibration amplitude remained at around 0.9 mm in our study.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The results obtained from MIMO radar interferometric processing were used as a benchmark and for comparison. Previous studies have shown that radar observations exhibit a high correlation with vision-based methods and accelerometers, with a maximum error of approximately 0.02 mm [5,7]. Our simulations revealed that while the resolutions of the AoA and vibration frequency improved with an increasing observation length, the resolution of the vibration amplitude remained at around 0.9 mm in our study.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, radar is insensitive to weather and lighting conditions and capable of penetrating through fog or smoke, thus significantly surpassing optical sensors [1]. As a result, studies in SHM are increasingly exploring radar remote sensing across various domains, including civil structures such as bridges [2] and buildings [3], tall structures such as towers [4] and wind turbines [5], cultural heritage [6], and industrial structures such as pipelines [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Paula Helming from the University of Bremen employed a ground-based laser scanner with a horizontal alignment line scanning mode to measure the tower and determined its axial and lateral deformation results through a least square fitting approach [12]. In 2023, Andreas Baumann-Ouyang from ETH Zürich used synthetic aperture radar to identify the tower's main frequency and to measure its deformation state [13]. These measurement methods require external auxiliary equipment and have high environmental requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The method of monitoring surface displacement is usually used for the construction safety of goaf, as shown by Zhuang and Qu (2022). Andreas et al (2023) used MIMO-SAR sensors to provide accuracy and economy in structural displacement monitoring; Zhang et al (2023) proposed the Time-Series InSAR and Hurst Index method to provide a new idea for ground deformation monitoring; Ju et al (2023) adopted the TDT method to better eliminate the temperature delay effect; Ren et al (2023) proposed that the distributed optical fiber monitoring technology of Brillouin optical frequency domain analysis (BOFDA) has specific advantages in monitoring the excavation deformation of ultra-deep underground space; Ju et al (2023) adopted the TDT method to better eliminate the temperature delay effect. Some studies also provide methods to improve monitoring accuracy, such as the constrained total least squares (CTLS) method (Zhou et al, 2021), a novel robust AE/MS source location method (Rui et al, 2022a), a novel acoustic emission(AE) source localization method (Rui et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%